(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
Interests in HA/polymer composites for bone tissue engineering have escalated due to their excellent biological response to damaged tissues. HA/polymer composites have been researched as potential implant in bone defects and voids. In this paper, HA was co-precipitated with two polymers including wool keratin and alginate. By changing the concentrations of wool keratin solution, alginate solution and Ca2+ and PO3−4 solution, the ratios of inorganic and organic phase were changed. The final result shows that HA embedded in the organic phase well and HA nanoparticles grown on the surface of wool keratin and linear alginate macromolecules formed cross-linking around Ca2+ of HA nanoparticles.